Intercondylar Route of Prosthetic Infragenicular Femoropopliteal Bypass Has Better Primary, Assisted, and Secondary Patency but Not Limb Salvage Rate Compared to the Medial Route. (7th September 2016) - Grus, Tomas; Lambert, Lukas; Banerjee, Rohan; Grusova, Gabriela; Rohn, Vilem; Vidim, Tomas; Mitas, Petr
Abstract : Aim . To compare the differences between medial and intercondylar infragenicular femoropopliteal prosthetic bypasses in terms of their midterm patency and limb salvage rates. Methods . Ninety-three consecutive patients with peripheral arterial disease who underwent a simple distal femoropopliteal bypass using a reinforced polytetrafluorethylene graft were included in this retrospective study. The bypass was constructed in the intercondylar route in 52 of the patients (group A) and in 41 in the medial route (group B). Results . Median observation time of the patients was 12.7 (IQR 4.6–18.5) months. There were 22 and 24 interventional or surgical procedures (angioplasty, stenting, thrombolysis, thrombectomy, or correction of the anastomosis) performed to restore patency of the reconstruction in groups A and B, respectively (p = 0.14 ). The 20-month primary, assisted, and secondary patency rates and limb salvage rates were 57%, 57%, 81%, and 80% in group A compared to 21%, 23%, 55%, and 82% in group B (p = 0.0012, 0.0052, 0.022, and 0.44, resp.). Conclusion . Despite better primary, assisted, and secondary patency rates in patients with a prosthetic infragenicular femoropopliteal bypass embedded in the intercondylar fossa compared to patients with the medial approach, there is no benefit in terms of the limb salvage rate and the number of interventions required to maintain patency of the reconstruction.